INOVASI PELAYANAN KESEHATAN (PROSES INOVASI JEMPUT BOLA DI PUSKESMAS II PUNGGELAN KABUPATEN BANJARNEGARA) - Indah Noviyanti Sugiharto; Dyah Hariani (Jurusan Administrasi Publik, Fakultas Ilmu Sosial dan Ilmu Politik, Universitas Diponegoro, 2017)
Public service in the health sector becomes a strategic issue. Public service improvements in Indonesia nowadays tend to be slow. One of the way to improve the quality of health services is innovation. An innovation have the importance to realize quality services in the health sector as well as in basic health services at the Center for Public Health (Community Health Centre). One of the areas that implementate the innovation of health services in Puskesmas is Banjarnegara Region. Community of Health Centre II Punggelan in corporation with the government of Banjarnegara Regenc created Innovation Pick up service. This study aims to determine the process of innovation pick up the service in Community of Health Centre II Punggelan Banjarnegara know the factors driving and inhibiting innovation process pick up the service in Community of Health Centre II Punggelan Banjarnegara Region. The method used in this research is descriptive qualitative research method. Researchers use theory of Rogers to identify the innovation process of pick up theservicel and theory of Fontana to identify the inhibiting factors and factors driving the innovation of pick up the service. There are several obstacles found in pick up service Innovation: there is no clear structure chart, there is a small part of traditional society culture, the availability of human resources, especially ambulance drivers are limited. The advice given is to make innovation of Pick up service as a service for the general public not only for labor alone.